Strategi Pemasaran Digital Rumah Sakit di Era Industry 4.0 untuk Meningkatkan Pendapatan Di UPT. RSUD HANAU Kabupaten Seruyan - Siti Patimah; Khuzaini; Syahrial Shaddiq (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
The acceleration of digital technology advancement and the expansion of internet reach have fundamentally reconfigured the marketing domain, including the healthcare service industry. The Industry 4.0 era, characterized by automation, large-scale data analytics, and interconnectivity, requires hospitals to implement progressive digital marketing approaches to maintain relevance and strengthen their competitive advantage. This evolution is reinforced by shifts in consumption patterns, where individuals increasingly rely on digital platforms to obtain medical information and make decisions regarding healthcare facilities. This trend is evident in the substantial escalation of hospitals’ adoption of digital technologies to communicate with healthcare service users. Digital marketing, conceptualized as the effort to achieve marketing objectives through the utilization of digital technologies and media, now plays a crucial role in this context, especially since the majority of consumers actively seek online information about treatment options and healthcare providers. Following the COVID-19 pandemic, the adoption of digital marketing strategies has become indispensable, marked by a significant acceleration in the use of digital marketing within the healthcare sector. Projections indicate growth in both in-person visits and telemedicine services, which in turn will increase hospital revenue. This phenomenon highlights the urgent need for healthcare institutions not only to adopt but also to refine their digital marketing approaches to attract new patients and foster loyalty. However, the healthcare sector faces specific challenges in implementing digital marketing, including regulatory frameworks that have yet to fully adapt and a lack of transparency and knowledge management among hospital personnel.